Pre-Service Ece Teachers’ Experiences in Implementing Multicultural Education - Pratiwi, Hardiyanti; Haida, Rizki Noor; Riwanda, Agus; Minasyan, Sona (Analisa: Journal of Social Science and Religion, 2023)
This research explores the essential importance of pre-service early childhood education (ECE) teachers having a strong comprehension and proficiency in intercultural instruction. This research focuses on examining the practical experiences of 168 pre-service ECE teachers from four institutions in Kalimantan. The main objective is to investigate how these teachers negotiate the implementation of multicultural education throughout their field placements. The research utilizes a descriptive quantitative research methodology by conducting surveys. Pre-service ECE teachers utilize a variety of methods to introduce and commemorate cultural diversity among young learners. These activities encompass field visits, media exploration, cultural performances, and storytelling to cultivate comprehension and admiration for diverse cultures. Although a few individuals encounter difficulties when carrying out tasks, the majority enthusiastically adopt interactive methods to enhance their experiences and expand their viewpoints. The assessment of multicultural education entails the quantification of engagement, comprehension, and reactions, thereby emphasizing specific domains that require enhancement. Efforts to tackle negative attitudes focus on promoting inclusive dialogues and cooperative endeavours, while refraining from punitive actions. Engaging parents, cultivating intercultural comprehension, facilitating discourse, and commemorating festivals all contribute to establishing inclusive educational environments where diversity is respected and celebrated. This research emphasizes the crucial significance of a comprehensive approach to multicultural teaching for pre-service ECE teachers. It also highlights the necessity of ongoing evaluation to enable the continuous enhancement of practices in this important educational field.